Factors Related to The Low Motivation of Mothers to Bring Babies/ Toddlers to Watermelon Posyandu in Environment IV Siborang Village Padang Sidimpuan City in 2019 - Normayanti Rambe (Institute of Computer Science (IOCS), 2021)
Posyandu is a form of community participation in the field of health managed by cadres with the target of all members of the community. The study aims to analyze the relationship of factors related to the low motivation of mothers to bring their babies/toddlers to Posyandu Watermelon in Environment IV Siborang Village in 2019. Design analytical survey research using the cross-sectional approach. The population in the study was all mothers who had babies/ toddlers in Ward IV Siborang Village as many as 73 people. Sampling techniques are performed using Total Sampling. Data analysis uses univariate and bivariate tests with Chi-Square. The results showed the occupational variable had a significant relationship with the p-value of 0.004< 0.05; education level variables have a significant relationship with p-value 0.011 < 0.05; and knowledge has a significant relationship with the value of p-value 0.040< 0.05 with the low motivation of the mother to bring her baby/ toddler to Posyandu Watermelon.It is recommended to the community, especially mothers, to be more active in seeking more information about the importance of bringing their babies/toddlers to Posyandu according to their age.